Numerical investigation of smoke contamination in atrium upper balconies at different down stand depths - Hasnain, S.A. (Tsinghua University Press, 2017)
Smoke contamination in upper balconies of shopping mall atriums presents a significant hazard to occupants by affecting evacuation and risking lives. Past research investigated the effects of varying balcony breadth, fire compartment opening width and fire size on smoke contamination. However, effects of varying the down stand depth at the fire compartment opening on smoke contamination have not been investigated. The down stand structure is widely used in shopping malls shops to display the trade names. This research investigates the effect of down stand depth on smoke contamination occurrence and severity in atrium upper balconies by varying the down stand depth together with the previously investigated parameters by utilizing Fire Dynamic Simulator (FDS), a computational fluid dynamics (CFD) software. Results demonstrated that the extent of smoke contamination increased with increased down stand depth. CFD simulation results showed that as down stand depth increased, from no down stand to 0.1 m in 1/10 scaled model, smoke severity increased by up to 40. An empirical correlation was also developed to predetermine the smoke contamination height by relating the above mentioned variables in a single correlation. © 2016, Tsinghua University Press and Springer-Verlag Berlin Heidelberg.